SLC6A4 polymorphisms modulate the efficacy of a tryptophan-enriched diet on age-related depression and social cognition - Ugartemendia, Lierni; Bravo, Rafael; Reuter, Martin; Castaño, M. Yolanda; Plieger, Thomas; Zamoscik, Vera; Kirsch, Peter; Rodríguez, Ana B. (Clinical nutrition, 2021)
Background & aims - In a placebo controlled study we sought to determine if a four-weeks tryptophan-enriched diet is able to improve age-related depression or social cognitive impairment, depending on polymorphisms located in the promoter region of Solute Carrier Family 6 Member 4 (SLC6A4), also known as serotonin transporter (SERT1) gene. - Methods - 91 young volunteers (age: 21 ± 2 yrs) and 127 above 50 years old (58 ± 6 yrs) healthy volunteers completed the study. Participants from the placebo and tryptophan group followed the same protocol. Before starting the study blood samples, to measure serotonin-transporter-linked polymorphic region (5-HTTLPR) and rs25531 polymorphisms, were collected. In addition, before and after completing the study urine samples (to measure 5-hydroxyindolacetic acid (5-HIAA) were taken, while psychological questionnaires (to assess depression and social cognition levels), and a one week dietary record (to calculate the tryptophan (TRP) intake) were assessed. - Results - The triallelic approach of SLC6A4 showed that in S'S´ subjects there was a positive correlation between TRP intake and 5-HIAA levels. Age of participants, SLC6A4 genotype, and experimental condition were important factors contributing to the outcome of depression and social cognition. - Conclusions - 5-HTTLPR and rs25531 polymorphisms play a key role in the response to the TRP- based nutritional intervention, improving only age-related depressive symptoms and empathy in S'S´ subjects who have a higher risk to show signs of depression during their lifetime.
Gesehen am 11.08.2021